2003
DOI: 10.1289/ehp.5756
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between environmental exposures to phthalates and DNA damage in human sperm using the neutral comet assay.

Abstract: Phthalates are industrial chemicals widely used in many commercial applications. The general population is exposed to phthalates through consumer products as well as through diet and medical treatments. To determine whether environmental levels of phthalates are associated with altered DNA integrity in human sperm, we selected a population without identified sources of exposure to phthalates. One hundred sixty-eight subjects recruited from the Massachusetts General Hospital Andrology Laboratory provided a seme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
145
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(160 citation statements)
references
References 40 publications
8
145
3
Order By: Relevance
“…3,10,[20][21][22] We focused on describing characteristics of apoptosis: mainly morphological changes (e.g., condensation, budding and cellular fragmentation) and biochemical alterations (i.e., DNA cleavage using Comet Assay Kit, Trevigen, Gaithersburg, MD, USA). Analysis of the comets to generate quantitative data was performed using a computer-based program (Duty et al 36 VisComet; Impuls Computergestutzte Bildanalyse GmbH, Gilching, Germany). The percentage of oocytes that underwent apoptosis out of the total number of oocytes cultured per drop in each experiment was then calculated.…”
Section: Characteristics Of Apoptosismentioning
confidence: 99%
“…3,10,[20][21][22] We focused on describing characteristics of apoptosis: mainly morphological changes (e.g., condensation, budding and cellular fragmentation) and biochemical alterations (i.e., DNA cleavage using Comet Assay Kit, Trevigen, Gaithersburg, MD, USA). Analysis of the comets to generate quantitative data was performed using a computer-based program (Duty et al 36 VisComet; Impuls Computergestutzte Bildanalyse GmbH, Gilching, Germany). The percentage of oocytes that underwent apoptosis out of the total number of oocytes cultured per drop in each experiment was then calculated.…”
Section: Characteristics Of Apoptosismentioning
confidence: 99%
“…Although single spot urine sample was usually used for exposure assessment [7,[13][14][15][16][17], concern has been raised over whether monoester concentration in single spot urine represents the subject's long-term exposure to phthalate esters because biological half-life in human body is short. Hoppin et al [18], Hauser et al [19], and Teitelbaum et al [20] reported utility of single spot urine for phthalate esters exposure assessment; however, Fromme et al [21] did not.…”
Section: Introductionmentioning
confidence: 99%
“…Sperm DNA damage was measured using neutral comet assay. In an analysis of 168 males (Duty et al 2003b), there was an exposure-response relation between MBP levels and sperm motility and concentration. Monobutyl benzyl phthalate (MBBP) levels were inversely associated with sperm concentration.…”
Section: Gonadal Hormones and Semen Qualitymentioning
confidence: 99%
“…In the regression analysis fT decreased significantly with increasing total phthalate ester score. Duty et al (2003aDuty et al ( , 2003bDuty et al ( , 2004Duty et al ( , 2005 and Hauser et al (2006) conducted a series of studies in male partners of subfertile couples recruited at an infertility clinic (US). They estimated associations between blood and urinary biomarkers of exposure to phthalates and various measures of semen quality and morphology.…”
Section: Gonadal Hormones and Semen Qualitymentioning
confidence: 99%